Beyond donkeys and elephants minor political parties in contemporary American politics - Davis, Richard 1955- (University Press of Kansas, 2020)
"The 2016 presidential election was dramatic in its outcome-the surprise election of Donald Trump. However, another surprise outcome was the increasing share of the vote won by minor parties and independent candidates. Gary Johnson, the Libertarian candidate, garnered 3.3 percent of the vote. That was the best performance by a minor party candidate since Ross Perot's 1996 Reform Party bid. Jill Stein, the Green Party candidate, won one percent of the vote. At the state level, the rejection of the two major party candidates in some places was even more profound. In three states, the non-major party candidates combined won over 10 percent of the vote. Voters in some states increasingly are electing candidates who do not belong to either of the two major parties. Currently, there are two independent members of the U.S. Senate-Bernie Sanders of Vermont and Angus King of Maine. Moreover, the percentage of Americans supporting the creation of a third party has reached new highs. In September 2017, according to a Gallup survey, 61 percent of Americans said a third party is needed. With so much dissatisfaction with the two major parties and so much interest in third party alternatives, there is a need for a fresh look at the current political party alternatives in the United States. The "Other" Parties describes the contemporary party landscape beyond the Republicans and Democrats, with chapters discussing minor parties at national, regional, and state levels. The chapters cover both the well-known alternatives-including the Green, Constitution, and Libertarian Parties-and niche, state-level parties, such as the Mountain Party in West Virginia, the Vermont Progressive Party, the Moderate Party of Rhode Island, and the United Utah Party"--